PROFIL MAHASISWA DENGAN TUGAS GANDA KULIAH DAN BEKERJA - ramdan homaedi; mafruhah mafruhah; anis tri yuliana (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2022)
Students have important roles in realizing the ideals of national development, meanwhile universities are educational institutions that are formally assigned the task and responsibility of preparing students in accordance with the goals of higher educators. The purpose of this research is to find out the extent to which students who study while working delay while completing their thesis. And also to know the negative impact of procrastination essay. The research conducted by this author is a qualitative descriptive study. In the process of collecting data, the author uses the method of observation, interviews, and documentation. Furthermore, for data analysis, the author uses qualitative descriptive, namely data in the form of writing or writing from the informants or respondents being studied in order to fully describe the phenomena in the field. Keywords: student profiles, dual assignments, lectures, work.